Experimental evidence and mechanism of action of some popular neuro-nutraceutical herbs. (October 2021) - Kumar, Ashish; Konar, Arpita; Garg, Sukant; Kaul, Sunil C.; Wadhwa, Renu
Abstract: Brain and neuronal circuits constitute the most complex organ networks in human body. They not only control and coordinate functions of all other organs, but also represent one of the most-affected systems with stress, lifestyle and age. With global increase in aging populations, these neuropathologies have emerged as major concern for maintaining quality of life. Recent era has witnessed a surge in nutritional remediation of brain dysfunctions primarily by "nutraceuticals" that refer to functional foods and supplements with pharmacological potential. Specific dietary patterns with a balanced intake of carbohydrates, fatty acids, vitamins and micronutrients have also been ascertained to promote brain health. Dietary herbs and their phytochemicals with wide range of biological and pharmacological activities and minimal adverse effects have gained remarkable attention as neuro-nutraceuticals. Neuro-nutraceutical potentials of herbs are often expressed as effects on cognitive response, circadian rhythm, neuromodulatory, antioxidant and anti-inflammatory activities that are mediated by effects on gene expression, epigenetics, protein synthesis along with their turnover and metabolic pathways. Epidemiological and experimental evidence have implicated enormous applications of herbal supplementation in neurodegenerative and psychiatric disorders. The present review highlights the identification, experimental evidence and applications of some herbs including Bacopa monniera, Withania somnifera, Curcuma longa, Helicteres angustifolia, Undaria pinnatifida, Haematococcus pluvialis, and Vitis vinifera, as neuro-nutraceuticals. Highlights: Brain disorders are complex and have limited treatment options. Neuro-nutraceutical herbs have emerged as natural remediation of brain disorders. Herbal bioactive compounds have multiple brain health promoting properties. Experimental and epidemiological evidences support nootropic potential of herbs. Phytochemicals act at epigenetic, gene and protein expression, and metabolic levels.